Soteriology in the Midst of the Climate Crisis: A Systematic- Constructive Approach to Cosmic Reconciliation - panggabean, Alex (Hikmat : Jurnal Agama Kristen, 2025)
The climate crisis demands a reconstruction of soteriology that goesbeyond individual justification to a cosmic reconciliation that touchesthe body, community, and creation. This study formulates a systematicconstructivesoteriological framework that binds various models ofsalvation—forensic, participatory/representative, Christus Victor,recapitulation (Irenaeus), theosis, and paschal ecology—across loci(creation–sin–redemption–ecclesiology–eschatology) and down to thedomains of liturgy–formation–diakonia–advocacy. The qualitativeconstructiveresearch design combines theological interpretation (Col1:15–20; Rom 8), tradition studies, congregational ethnography(observation of worship, liturgical artifacts, purposive interviews), andreading of local policies/ecologies. The abductive-thematic analysistakes place in stages: descriptive (thick description), correlational(model × loci × practice matrix), constructive (formulation ofpropositions & operational rubrics), and evaluative (member checkingand 6–8 week pilot).Results show increased participation in worship/formation, decreasedhousehold carbon footprint (tCO₂e/quarter), increase insorted/recycled waste, and expansion of green space/communitycompost after the implementation of ecological paschal liturgy(lament–confess–commit flow), sabbatical economic catechesis, carbonfasting/digital-consumption sabbath, and green diaconia SOP (urbanfarming, waste bank) tied to a micro-policy brief at the village level. Theevaluation confirms strong biblical fidelity and systematic coherence,medium–strong contextual adequacy, and high practical applicability.This study concludes that soteriology structured as cosmicreconciliation provides a conceptual foundation and replicableoperational tools for the church to take a real part in the renewal ofcreation in the era of climate crisis.